Analyzing the Relationship Between Capital Structure, Profitability, and Their Impact on Company Value in Consumer Goods Subsector Manufacturing Companies Listed on the Asean Stock Exchange - Laksono, Febri Suryo; Paniya, Paniya -; Zaenuddin, Achmad - (JOBS (Jurnal Of Business Studies), 2024)
This study investigates the impact of capital structure and profitability on the company value of consumer goods subsector manufacturing companies listed on the ASEAN Stock Exchange from 2019 to 2022. The primary objective is to determine how these financial metrics influence the valuation of firms in a highly competitive and dynamic market. Utilizing panel data analysis, this research analyzes 168 companies selected through purposive sampling based on specific criteria, including consistent financial performance and market capitalization. Descriptive statistics reveal significant variation in capital structures, with an average debt-to-equity ratio (DER) of 3.503 and profitability, measured by return on equity (ROE), averaging 1.253. The common effect, fixed effect, and random effect models were evaluated, with the random effect model deemed most appropriate based on Hausman and Breusch-Pagan tests. The regression analysis shows that both DER and ROE positively and significantly impact company value, as indicated by the price-to-book ratio (PBV). The findings underscore the importance of strategic financial decision-making in enhancing firm value. Higher DER suggests effective leverage use, while increased ROE indicates efficient management and strong financial performance, both contributing to higher firm valuations. This study contributes to the academic understanding of corporate finance within the ASEAN consumer goods sector and provides practical insights for managers, investors, and policymakers to optimize financial strategies and enhance competitiveness.